Diverse floodplain deposits of reworked loess in a monsoon climate (Hanzhong Basin, central China). (September 2021) - Vandenberghe, Jef; Yang, Xun; Wang, Xianyan; Wang, Shejiang; Lu, Huayu
Abstract: This paper describes an assemblage of diverse floodplain facies of reworked loess (facies b, c) in a Middle Pleistocene monsoonal setting of the Hanzhong Basin, central China. The vertical and lateral sedimentary sequences show changing energy conditions. Apart from the highest energy in the channel facies (facies a), a relatively high energy floodplain environment (facies b) prevailed in waterlogged conditions, with small, laterally migrating (sub)channels. Facies b generally interfingers with aggrading horizontal sheets of overbank deposits in alluvial pools and swamps in a floodplain with much lower energy (facies c), in which phases of stability (soil formation) occasionally interrupted overbank deposition. Reworked loess forms the main part of the floodplain deposits. The paleosols are considered to have been formed under low hydrodynamic conditions in an interglacial environment. These interglacial conditions follow the commonly assumed glacial conditions of channel facies a. The sedimentary successions in the floodplain show a recurrent composition and cyclicity between wet and dry floodplain sedimentation terminated by stability with soil formation. The cyclic rhythm of stacked high- and low-energy floodplain sediments is attributed to varied intensity of different hydrodynamic flooding events that may have been due to changing monsoonal rainfall or simple intrinsic fluvial behavior.